Dialektisch-behaviorale Therapie für Adoleszente = Dialectical behavioral therapy for adolescents - Reichl, Corinna; Kaess, Michael (Psychotherapeut, 2019)
Borderline personality disorder (BPD) is associated with substantial suffering, impairment in psychosocial functioning levels and severe burdens for affected adolescents and their relatives. Consequently, a standardized and tailored diagnostic procedure and intervention as early as possible are of great importance. The present article describes the diagnostic criteria and clinical symptoms of BPD and of the associated phenomena of non-suicidal self-injurious behavior and suicidal behavior. Furthermore, the principles and essential treatment elements of dialectical behavioral therapy for adolescents (DBT-A) along with their relevance for the treatment of core symptoms of BPD are presented. Finally, the article describes current research findings regarding the effectiveness of DBT-A and the concept of the outpatient clinic for adolescents with risk-taking and self-injurious behavior (AtR!Sk).